Analysis of the Influence of Leadership and Compensation Style on Employee Performance with Competence as an Intervening Variable at PT. Pelabuhan Indonesia - Agus May Suryanto; Hermien Tridayanti; Joko Suyono (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: Think about the role that employee competency plays in the relationship between leadership style, salary, and performance.